Cardiovascular Disease Risk Assessment Among Automobile Technicians At The Industrial Area In The Tamale Metropolis, Northern Region, Ghana - Bawa, E.M. (University Of Ghana, 2021)
Background: There is a rapid increase in the burden of CVD in Low and Middle-Income Countries (LMIC). The prevalence of its risk factors and early outcomes are reaching epidemic proportions in Ghana. The global risk function presented by the Framingham investigators estimates the risk of developing CVD and can be used to quantify risk and guide preventive care. Automobile technicians are constantly in contact with harmful chemicals in their work environment that impact their health negatively. Regular exposure to automotive pollutants increases the risk of developing atherosclerosis leading to adverse cardiovascular events among automobile technicians. Though total risk assessment is recommended and the rise in morbidity and mortality associated with CVD is noticeable, individuals and societies, particularly automobile technicians, have no idea of their level of risk. This results in limited and untargeted preventive measures. This study, therefore, aimed at assessing the risk of developing CVD in 10-years among automobile technicians at the industrial area in the Tamale Metropolis, Northern Region Methods: A cross-sectional study involving automobile technicians aged 20 years or older in the industrial area of the Tamale metropolis was carried out. A multi-stage sampling technique was used to select participants. Data on individual factors, risk factors, knowledge, attitude, and practices were collected with the aid of a semi-structured questionnaire. Anthropometric measurements were taken and blood samples were also collected for biochemical analysis. Using the Framingham Risk Scoring algorithm, the 10-year CVD risk for each participant was estimated. Data collected was analyzed using STATA 15 and results were presented as frequencies, proportions, and odds ratios in tables and graphs. Results: All the study participants (210) were males, with 36 years being the median age. The most prevalent risk factor for CVD was hypertension with a prevalence of 32.86%. Hypertension was significantly associated with diabetes (p = 0.016) and other risk factors. The prevalence of low, moderate, and high 10-year CVD risk was 80.0%, 11.43%, and 8.57%, respectively. The 10-year CVD risk varied significantly with age (p <0.001), years of work experience (p < 0.001), and the job category/specialty (p = 0.004). The majority of the participants had adequate knowledge (74.29%) and attitude (57.14%) towards cardiovascular disease risk factors and prevention with a few (<5%) engaging in good practices. Those with an adequate attitude had 87% reduced odds of having a high 10-CVD risk score when compared to those with inadequate attitudes. Conclusion: There was a high prevalence of CVD risk factors among the automobile technicians, with a fifth of them having a moderate to high 10-year CVD risk score. Whiles the majority of the participants had adequate knowledge and attitude scores, only a few had adequate practices scores on CVD risk factors and prevention. Adequate attitude had a reduced the 10-year CVD risk score among the automobile technicians.
MPhil. Applied Epidemiology And Disease Control
Keywords: Ghana; Cardiovascular Disease; Automobile Technicians; Tamale Metropolis